2015
DOI: 10.1016/j.scitotenv.2015.07.151
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic silver speciation as studied with fluorous-phase ion-selective electrodes: Effect of natural organic matter on the toxicity and speciation of silver

Abstract: The widespread application of silver in consumer products and the resulting contamination of natural environments with silver raise questions about the toxicity of Ag+ in the ecosystem. Natural organic matter, NOM, which is abundant in water supplies, soil, and sediments, can form stable complexes with Ag+, altering its bioavailability and toxicity. Herein, the extent and kinetics of Ag+ binding to NOM, matrix effects on Ag+ binding to NOM, and the effect of NOM on Ag+ toxicity to Shewanella oneidensis MR-1 (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 66 publications
3
38
1
2
Order By: Relevance
“…The relative impact of the NOM types used here on AgNP dissolution is also consistent with the results of our related study in which ISEs were used to measure Ag + binding to NOM in the absence of AgNPs. 24 Addition of PLFA to a Ag + solution significantly decreased the free Ag + concentration, indicating binding of NOM to Ag + , while SRHA and SRFA induced smaller decreases. In the present study, PVP-capped AgNPs were also observed to be less toxic than citrate-capped AgNPs, consistent with their significantly lower release of Ag + (Figure 3b).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The relative impact of the NOM types used here on AgNP dissolution is also consistent with the results of our related study in which ISEs were used to measure Ag + binding to NOM in the absence of AgNPs. 24 Addition of PLFA to a Ag + solution significantly decreased the free Ag + concentration, indicating binding of NOM to Ag + , while SRHA and SRFA induced smaller decreases. In the present study, PVP-capped AgNPs were also observed to be less toxic than citrate-capped AgNPs, consistent with their significantly lower release of Ag + (Figure 3b).…”
Section: Resultsmentioning
confidence: 92%
“…31 Three types of NOM were used: Suwannee River fulvic acid (SRFA) and Suwannee River humic acid (SRHA) have similar elemental compositions 32 (SI Table S1) and represent NOM fractions derived primarily from decomposition of vegetation. 33 Pony Lake fulvic acid (PLFA) represents NOM rich in sites with high affinity for metallic silver and Ag + (due to high sulfur and nitrogen content, 34 a subset of which has a high affinity for silver and Ag + ; 24 SI Table S1). It is derived exclusively from microbial matter decomposition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples were equilibrated on an end-over-end shaker (Heidolph Reax II) in darkness at 14 °C for 48 hours. According to previous studies made with soil materials 15,17,18 and isolated humic fractions 28 , this would enable equilibration of silver(I) ions in the soil suspensions. Long equilibration times (weeks-months), might result in ageing and transformation reactions 15,16 .…”
Section: Methodsmentioning
confidence: 99%